2002
DOI: 10.1046/j.1365-2273.2002.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of computerized tomography in the preoperative assessment of chronic suppurative otitis media

Abstract: Twenty patients awaiting mastoid surgery for chronic suppurative otitis media underwent preoperative high resolution computerized tomography (CT) of the temporal bones. The CT scans were compared with the intraoperative findings. CT was helpful in determining the anatomy of the middle ear and mastoid, and accurately predicted the extent of the disease process in the sinus tympani and facial recess. However, it was unable to distinguish between cholesteatoma, mucosal disease and fluid, and it contributed little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 2 publications
10
39
1
2
Order By: Relevance
“…Where our results differ is that some studies maintain that CT is not sufficient to diagnose cholesteatoma [1,5]. Computerized tomography may give an incorrect diagnosis in the early stage of cholesteatoma.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Where our results differ is that some studies maintain that CT is not sufficient to diagnose cholesteatoma [1,5]. Computerized tomography may give an incorrect diagnosis in the early stage of cholesteatoma.…”
Section: Discussioncontrasting
confidence: 90%
“…The exact role of CT in the preoperative assessment of patients with chronic otitis media is controversial [5]. Some authors have reported a high degree of accuracy in the pathological diagnosis of ossicular chain and inner ear conditions [6] and others have concluded that CT has poor ability to diagnose cholesteatoma and should not be relied on to visualize abnormalities of the previously mentioned structures [7].…”
Section: Discussionmentioning
confidence: 99%
“…100%.This finding is in agreement with that of Reilly et al [12] and Shaffer et al [14] However we could not distinguish cholesteatoma from other soft tissue disease .Walshe et al [15] in their study could not distinguish between mucosal disease and cholesteatoma. Cholesteatoma characteristically causes bone erosion and when this feature was present in association with a soft tissue mass on CT both Jackler et al [6] and O'Donoghue et al [9] found cholesteatoma to be present in 80% of cases explored.…”
Section: Soft Tissue Masssupporting
confidence: 92%
“…The exact role of HRCT in the preoperative assessment of patients with chronic otitis media is controversial [3].…”
Section: Discussionmentioning
confidence: 99%